Optimasi Penjadwalan Pegawai Balai Penelitian Tanaman Jeruk Dan Buah Subtropika (Balitjestro) Untuk Wisata Edukasi Petik Jeruk Menggunakan Algoritme Genetika - Annisa Amalia Nur'aini; Agus Wahyu Widodo; Muh. Arif Rahman (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Educational tourism is an activity where tourists can interact directly with certain tourist objects related to tourist attractions. Balitjestro is one of the technical implementing units under the Ministry of Agriculture which opens â€œWisata Edukasi Petik Jerukâ€ every time the harvest arrives. This activity requires the allocation of resources as officers taken from all employees at Balitjestro. In one day, ideally this activity requires 106 officers while the total number of employees is only 75 (Sutopo, 2018). Because of limited human resources, it is necessary to do the optimal scheduling to allocate tourism officers. Manually scheduling takes a long time because it has to match the availability of free time for each employee. Apart from that, several roles are needed, including tour guides, guards, cashiers and grapefruit weighers. One method that can be used for optimization problems is a genetic algorithm. This method consists of several stages including initial population initialization, reproduction, evaluation and selection. The results of this study state that genetic algorithms are able to provide results of employee scheduling for duty during tourism activities with the highest accuracy value that can be achieved at 92.72%. While the overall system accuracy is 91.90%.